Product lifecycle management (PLM) : a digital journey using industrial internet of things (IIoT) - Elangovan, Uthayan (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
"This book provides a summary of the essential topics of Product Lifecycle Management (PLM) along with Industrial Internet of Things (IIoT) in the era of Industry 4.0"--
OCLC-licensed vendor bibliographic record.
Keywords: Product life cycle -- Data processing; Internet of things -- Industrial applications; COMPUTERS / Internet / General; TECHNOLOGY / Manufacturing